The influence of soil resistivity in the area of underground pipeline on the efficiency of cathodic protection - V. G. Kiselev; A. A. Kalyutik (Известия высших учебных заведений: Проблемы энергетики)
In the article analysis and describes the main factors influencing the energy efficiency of cathodic protection determined by the ratio of the conductivity of the electrolyte surrounding the underground (submerged) metallic structure (piping) and its polarization resistance. Our results are valid primarily if the pipeline of a modern high-quality insulation with high dielectric properties is made, for example, based on polymers or their compositions and are designed primarily for their use in protection against electrochemical corrosion of underground pipelines.